MITIGATING SEISMIC VULNERABILITY OF WIND TURBINES USING TUNED MASS DAMPERS AND INERTERS - Fitzgerald, Breiffni; Broderick, Brian; Hickey, John; McAuliffe, James (My University, 2024)
Seismic loads can cause significant damage to wind turbines, leading to costly repairs and downtime. In this study, we investigate the response of a 150m tall, 15-MW wind turbine to seismic loads and propose a vibration control strategy using tuned mass dampers (TMDs) and tuned mass damper inerters (TMDIs). Inerter-based dampers have recently been applied to improve the seismic performance of structures such as multi-storey buildings and bridges and have been used for vibration control of wind turbines subjected to turbulent aerodynamic loading. Compared to traditional TMDs, TMDIs have been shown to be more effective in reducing structural responses whilst also reducing the damper stroke required for operation and can therefore be used in structures with limited space available for dampers such as wind turbine towers. This study develops a finite element (FE) model of a 15-MW wind turbine. The FE model was constructed using Abaqus software, leveraging Solidworks geometry provided by the International Energy Agency (IEA). The model incorporates detailed representations of the tower, foundation, and blades, utilising a combination of hexahedral and tetrahedral elements to accurately capture their complex geometries. The meshing process involved refining the mesh in critical regions to capture local stress concentrations and deformation patterns. Boundary conditions are carefully defined to capture the dynamic behaviour of the system while considering relevant degrees of freedom and connections between components. The model has been verified via a modal analysis comparing both the first natural frequency and mode shape of the tower with those specified by the IEA. Dynamic time-domain simulations of earthquake records of varying magnitudes and frequencies have been performed using the finite element model and a fragility analysis is presented to demonstrate the clear benefits of installing dampers in wind turbines subjected to seismic loads. The results of the study show that the TMDI controlled structure outperforms the TMD controlled system in terms of reducing the seismic response of the wind turbine. The findings of this study may inform the design of future wind turbines and other large-scale structures in seismic-prone regions. Overall, this study highlights the importance of considering the seismic response of wind turbines and proposes an effective mitigation strategy that can enhance their resilience to seismic events.
18th World Conference on Earthquake Engineering
PUBLISHED
Milan, Italy
Keywords: Smart & Sustainable Planet; Renewable energy; Structural Engineering